1995
DOI: 10.3109/00016489509125212
|View full text |Cite
|
Sign up to set email alerts
|

The Auditory, Vestibular, and Oculomotor System in Facioscapulohumeral Dystrophy

Abstract: Verhagen WIM, Huygcn PLM, Padberg GW. The auditory, vestibular, and oculomotor system in facioscapulohumeral dystrophy. Acta Otolaryngol (Stockh) 1995; Suppl 520: 140.142.Auditory, vestibular and oculomotor function tests were performed in 14 FSHD patients (7 men, 7 women, aged 19 -74 years) with autosomal dominant facioscapulohumeral dystrophy (FSHD) due to chromosome 4q35 associated DNA rearrangements. (Cochlear) sensorineural hearing loss (SNHL) in excess of that expected for their age was found in 6 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…We focused on Ret signalling as a potential mediator of DUX4-induced muscle pathology for several reasons. FSHD is characterised by the often asymmetric wasting of facial, shoulder and upper arm muscles (Tawil, 2008), and can be associated with several non-muscle tissue pathologies including sensorineural hearing loss and retinal vasculopathies (Verhagen et al, 1995). Development of the auditory system, retinal patterning and facial muscles have been shown to depend on Ret signalling in a number of species.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on Ret signalling as a potential mediator of DUX4-induced muscle pathology for several reasons. FSHD is characterised by the often asymmetric wasting of facial, shoulder and upper arm muscles (Tawil, 2008), and can be associated with several non-muscle tissue pathologies including sensorineural hearing loss and retinal vasculopathies (Verhagen et al, 1995). Development of the auditory system, retinal patterning and facial muscles have been shown to depend on Ret signalling in a number of species.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of later onset FSHD using audiometry have demonstrated hearing deficits in many later onset FSHD patients in addition to those with “Coates” syndrome, suggesting that impaired hearing function is more common than expected in FSH muscular dystrophy. 51,62,93 Thus, all patients with FSHD should have screening audiometry and ophthalmologic evaluation.…”
Section: Physical Examinationmentioning
confidence: 99%
“…5 The reasons these disease in particular have more pain are not clear but they involve membrane-related pathology, and both disorders have underlying genetic expansion-type mutations and are multisystem disorders. 40 …”
Section: Disease-specific Pain Traitsmentioning
confidence: 99%